Annual Plan-1978-79 Andaman and Nicobar - Planning Commission (Planning Commission, 1978)
During the Five Year plan on outlay of Rs. 392.20 lakhs was earmarked for the implementation of Forestry Schemes including Rs. 170 lakhs as Equity shares for the Andaman and Nicobar Islands Forest & Plantation Development Corporation. As per the instruction of the Planning Commission the Fifth Five Year Plan is to be terminated in the year 1977-78 and Five Year Flan has to be implemented with to 1982-83. Thus the current year is the last year of the Fifth Five Year Plan the Total Fifth Plan expenditure is anticipated to 139.522 lakhs for the Forestry Schemes and Rs. 103 lakhs as Equity Share for the Corporation, a total of Rs. 241.522 lakhs. on the basis of the provisions of the Fifth Five Year Plan, an amount of Rs. 149.678 lakhs is still available for 1968-79 but as per the instructions of the Planning Commission, the annual Plan for 1978-79 proposed is only for Rs. 129.032 lakhs.
Andaman and Nicobar